Comparative exploitation characteristics of some types of machines in making haylage - Jugović Milan; Radivojević Dušan; Koprivica Ranko; Lalović Miroslav; Jakišić Tanja (Agroznanje, 2013)
This paper presents the results of two different types of machines used for preparing haylage: haylage line with SIP Pioneer 17 self-loading trailer with knives in a trench silo and Deutz -Fahr GP 2.50 round bale press for large round bales and wrapping bales in stretch plastic foil. Tests were performed in production conditions on the family farm in Mokro (the Republic of Srpska) with the aim to compare exploiting characteristics of both types of machines. The following parameters were considered: speed, efficiency and the share of each operation. To assess the effectiveness of individual operations, we performed timing analysis (time-motion study) and examined individual working operations i.e. collecting aerated mass and transport, unloading and storage. Under the production conditions, Pioneer 17 self-loading trailer in the aggregate with a tractor IMT 540 Deluxe achieved a speed of 1.73 km/h. Surface-based field capacity of the machine in time-motion study was 0.30 ha/h. Time-motion has found that the largest part of time was spent on trailer filling, 46.67%, as well as in downtime, 25.05%. Deutz-Fahr GP 2.50 round bale press in the aggregate with an IMT 577 DV tractor achieved a speed of 1.62 km/h with the surface field capacity of machine at 0.45 ha/h. Based on the time-motion study, most of the time was spent on the process of pressing and chamber filling with plant mass, 77.23%, and the minimum time was spent on the process of tying the bales, 5.31% of the total time.